Soil carbon: a critical natural resource widescale goals, urgent actions - Nziguheba, Generose; Vargas, R.; Bationo, B. André; Black, H.; Buschiazzo, Daniel E.; Brogniez, Delphine de; Joosten, H.; Melillo, J.; Richter, D.; Termansen, Mette (CAB International, 2015)
Across the world, soil organic carbon (SOC) is decreasing due to changes in land use such as the conversion of natural systems to food or bioenergy production systems. The losses of SOC have impacted crop productivity and other ecosystem services adversely. One of the grand challenges for society is to manage soil carbon stocks to optimize the mix of five essential services – provisioning of food, water and energy; maintaining biodiversity; and regulating climate. Scientific research has helped develop an understanding of the general SOC dynamics and characteristics; the influence of soil management on SOC; and management practices that can restore SOC and reduce or stop carbon losses from terrestrial ecosystems. As the uptake of these practices has been very limited, it is necessary to identify and overcome barriers to the adoption of practices that enhance SOC. Actions should focus on multiple ecosystem services to optimize efforts and the benefits of SOC. Given that depleting SOC degrades most soil services, we suggest that in the coming decades increases in SOC will concurrently benefit all five of the essential services. The aim of this chapter is to identify and evaluate wide-scale goals for maximizing the benefits of SOC on the five essential services, and to define the short-term steps towards achieving these goals. Stopping the losses of SOC in terrestrial ecosystems is identified as the overall priority. In moving towards the realization of multiple SOC benefits, we need to understand better the relationships between SOC and individual services. Interactions between services occur at multiple spatial scales, from farm through landscape to subnational, national and global scales. Coordinated national and international responses to SOC losses and degradation of the five essential services are needed to empower SOC actions at local levels that have benefits on the larger scales. We propose the creation of a global research programme to expand the scientific understanding of SOC and its contribution to the five essential services. This should address the challenges and uncertainties associated with the management of SOC for multiple benefits. This research programme must include a strong education and outreach component to address concerns to different communities outside academia.